The Relationship between Plasma Hypocretin Levels and Sleep Disorders in Patients with Parkinson's Disease - Ahmad Afdal; Syarif Indra; Hendra Permana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: There are many areas of brain degeneration in people with Parkinson's disease. The dopaminergic degeneration process in the midbrain causes early symptoms of sleep disturbances. Hypocretin produced by the hypothalamus is involved in the pathophysiology of Parkinson's disease. Some research results regarding the relationship between plasma hypocretin levels and sleep disorders in patients with Parkinson's disease are still controversial. Method: This research is a cross sectional study in Neurology Polyclinic Dr. M. Djamil Padang and Network Hospital. All research subjects measured hypocretin levels and sleep disorders using the Epworth Sleepiness Scale. Statistical analysis was performed on a computerized basis using IBM SPSS statistics version 23.0 for windows. Result: A total of 60 patients with Parkinson's disease were included in this study, 30 subjects experienced sleep disorders and 30 others had no sleep disorders. There was a significant difference in lower plasma hypocretin levels in the Parkinson's group with sleep disorders, namely 81.817 ± 22.770 and in the group without sleep disorders, plasma hypocretin levels were found to be 255.416 ± 226.590 (p = 0.000). There was no statistical difference in clinical degree, age, duration of illness between the Parkinson's group with sleep disorders and the group without sleep disorders p > 0.05. Conclusion: There is a significant difference in hypocretin levels against the sleep disorder group in people with Parkinson's disease. In this study, there was no association between age, clinical degree of Parkinson's disease, and duration of Parkinson's disease and sleep disturbances. Degeneration in the olfactory bulb area, hypothalamus, and brainstem can precede dopaminergic degeneration in the midbrain and cause sleep disturbance symptoms.